Dynamics Of Economic Development Disparities A New Perspective In Regional Analysis - Yuliana; Astuti Prihatiningsih; Ari Yopi Ispa (CV Putra Publisher, 2024)
Disparities in economic development between regions are a complex and challenging phenomenon in the context of regional development. This article aims to provide a new perspective in analyzing disparities in economic development from a regional perspective, using a literature review method. Through an in-depth review of various literature sources, this article identifies critical factors that cause economic disparities between regions, such as differences in natural resources, infrastructure, and regional economic policies. Apart from that, this article also discusses the impact of economic disparities on overall economic growth. In formulating a new perspective, this article proposes a more holistic and inclusive approach to addressing economic development disparities. This approach involves the critical role of government, the private sector, and society in strengthening cooperation between regions, increasing access to resources, and promoting sustainable and equitable economic growth. This article also identifies several research areas that need further attention, such as analysis of the impact of technology on economic disparities and evaluation of the effectiveness of regional development policies. Thus, this research can significantly contribute to understanding and addressing disparities in economic development between regions and stimulating further discussion in the context of sustainable regional economic development.